Eksperimen Pembelajaran Matematika Dengan Model Discovery Berbasis Mind Map dan Concept Map Ditinjau dari Kemampuan Komunikasi Matematis Siswa - Oktaviani, Putri; , Dra. Nining Setyaningsih, M.Si; , Sri Rejeki, M.Pd, M.Sc (2015)
This study aims to examine and analyze: (1) the difference on the effect of Discovery model based on Mind Map and Concept Map on students' mathematics achievement (2) the difference on the effect of the level of students' mathematical communication skills on students' mathematics achievement (3) the effect of interaction between learning models and the level of students' mathematical communication skills on students' mathematics achievement. This study is a quantitative research with a quasi eksperimental design. The study population was all students of grade X SMK Negeri 9 Surakarta academic year 2014/2015. Two classes were chosen as the sample of this study by cluster random sampling. The data collection was conducted using test, questionaire and documentation. The data were analyzed using different number of cell analysis of variance with α = 5%. Based on the analysis, it can be concluded that: (1) there is significant difference on the effects of Discovery model based on Mind Map and Concept Map on students' mathematics achievement, (2) there is significant difference on the effects of the level of students' mathematical communication skills on students' mathematics achievement, (3) there is no effect of interaction between learning model and the level of students' mathematical communication skills to mathematics achievement.